Noncontact lateral-force gradient measurement on Si(111)-7×7 surface with small-amplitude off-resonance atomic force microscopy - Atabak, M.; Ünverdi O.; H.O., Özer; Oral, A. (American Vacuum Society, 2009)
In this work, the authors report on a quantitative investigation of lateral-force gradient and lateral force between a tungsten tip and Si(111)-(7×7) surface using combined noncontact lateral-force microscopy and scanning tunneling microscopy. Simultaneous lateral-force gradient and scanning tunneling microscopy images of single and multiatomic step are obtained. In our measurement, tunnel current is used as feedback. The lateral-stiffness contrast has been observed to be 2.5N∕m at a single atomic step, in contrast to 13N∕m at a multiatomic step on Si (111) surface. They also carried out a series of lateral stiffness-distance spectroscopy, which show a sharp increase in tip-surface interaction stiffness as the sample is approached toward the surface.
Keywords: Silicon; Tungsten tips; Tip-surface interactions; Atomic forces; Lateral forces; Tungsten; Atomic steps; Si (1 1 1); Stiffness; Force gradients; QC Physics; Tunnel currents; Lateral-force microscopies; Lateral stiffness; Scanning; Off resonances; Sharp increase; Noncontact; Scanning tunneling microscopy; Quantitative investigations